The Effect of Corn Starch Edible Coating and Immersion Time on Quality of Minimally Processed Pineapple - Nia Nazrah Hasibuan; Ismed Suhaidi; Ridwansyah Ridwansyah (Jurnal Rekayasa Pangan dan Pertanian, 2016)
The objective of this research was to find out the effect of corn starch edible coating and immersion time on quality of minimally processed pineapple. Method used in this research was completely randomized design (CRD) with 2 factors, i.e; the concentration of starch (P) : (1%, 2%, 3%, and 4%) and immersion time (L) : (1 minute, 2 minutes, 3 minutes, and 4 minutes). Parameters analyzed were total soluble solid, total acid, vitamin C content, moisture content, fiber content, brightness level, organoleptic values of flavor and taste, texture score, and color score.          The results showed that the starch concentration had highly significant effect on total soluble solid, total acid, vitamin C content, and texture score. Immersion time had highly significant effect on total soluble solid, total acid, vitamin C content, organoleptic values of flavor and taste, texture score and color score. The interaction of starch concentration and immersion time had significant effect on total soluble solid. The starch concentration of 1% and immersion time of 1 minute gave the best quality of minimally processed pineapple.